Comparative Anatomical Study Between the Human and Swine Liver and Its Importance in Xenotransplantation - Ntonas, Athanasios (Cureus, 2020)
The liver is a multifunctional organ; due to its functional and structural complexity, there are many factors that may lead it to function inadequately, a state called liver failure. Transplantation is the only appropriate therapy for patients in cases of liver failure. However, there are many limitations to this treatment, and the scientific community has considered methods based on pigs because of their unique structural and cellular compatibility with humans. In this review, we conducted an anatomic comparative study of the liver’s parenchyma and vascular network between humans and pigs to extract useful information for xenotransplantation and autologous cell or organ generation in pigs. We reviewed articles from 2007 to 2019 and used the databases of Scopus, PubMed and Google Scholar. We concluded that, despite the difference concerning the shape of the human and pig livers, the number of segments and the bile and vascular system are similar, making the pig liver useful in experimental surgery for xenotransplantation.